Sustainable purchase behavior for products of disabled entrepreneurs: The roles of product quality, empowerment, and innovation behavior - Epriliyana, Nike Norma; Yulisetiarini, Diah; Irawan, Bambang; Nurhayati (International Journal of Management and Sustainability, 2026)
This study examines the influence of empowerment, innovative behavior, product quality, and pricing strategy on sustainable purchase behavior for products of disabled entrepreneurs. The sustainability of businesses run by disabled entrepreneurs is a crucial factor in ensuring their long-term survival. The research approach employed is quantitative. Data analysis utilizes Structural Equation Modeling (SEM) with SPSS-AMOS 24 software. The respondents consist of 145 consumers. A purposive sampling technique was used to select participants. Data collection was conducted using an electronic questionnaire. The research concluded that empowerment and product quality positively influence innovation behavior and sustainable purchase behavior for products of disabled entrepreneurs. However, the pricing strategy did not have a positive impact on sustainable purchase behavior for these products. The sustainable empowerment of disabled entrepreneurs, whether carried out by the government or the community, played a positive role in promoting sustainable purchase behavior and ensuring the continuity of their businesses. Empowerment has a positive influence on the innovative behavior of entrepreneurs with disabilities. Consumer decisions to make repeat purchases are based on empowerment, innovative behavior, and product quality. These are essential indicators of the sustainability of products made by entrepreneurs with disabilities. The government needs to strengthen entrepreneurial skills through sustainable empowerment programs, increased access to capital, and infrastructure improvements to promote sustainable purchasing behavior for products of disabled entrepreneurs.